The Influence of Motivation, Training, Work Environment and Compensation on Employee Performance - Mofu, Yason Yikwa; Noch, Muhamad Yamin; Khotimah, Khusnul (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the influence of motivation, training, work environment, and compensation on the performance of social assistants in the Joint Business Groups (KUBE) program in Papua. It seeks to answer how these factors individually and collectively impact the effectiveness of social assistants in enhancing community welfare. Research Design and Methodology: Utilizing an explanatory research design, this quantitative study employed a survey model with questionnaires distributed to 87 social assistants in Jayapura City, Jayapura Regency, Keerom Regency, and Sarmi Regency. The research examined the relationships between motivation, training, work environment, and compensation as independent variables and social assistants' performance as the dependent variable. Data analysis included validity, reliability, classical assumption tests, and multiple regression analysis using SPSS. Findings and Discussion: The results indicate that motivation, training, work environment, and compensation significantly impact the performance of social assistants both individually and collectively. Motivation enhances commitment and task outcomes; training improves technical skills and confidence; a supportive work environment boosts productivity, and fair compensation increases job satisfaction. These findings align with existing theories and underscore the importance of these factors in optimizing employee performance in social assistance programs. Implications: The study suggests that integrated strategies encompassing motivation programs, continuous training, supportive work environments, and fair compensation are crucial for enhancing the performance of social assistants. Policymakers and managers should focus on these areas to improve the effectiveness of social assistance programs and ultimately enhance community welfare in Papua. Future research should investigate the long-term effects and potential mediating factors to refine these strategies further.